How the District Court has applied the principles of due diligence – and what this means for senior leaders - Barton, Francois (New Zealand Journal of Health and Safety Practice, 2025)
Many senior leaders know all too well the duty of due diligence – be that in a financial or legal context. When it comes to health and safety, however, the duty of due diligence has until now been largely untested. Since the introduction of the Health and Safety at Work Act 2015 (HSWA) CEOs, senior leaders and Directors have been aware of the new duties placed on them as individuals, but with a lack of case law or precedent that awareness or focus may have drifted.